EFFECT OF ETHANOL-GASOLINE MIXES ON PERFORMANCES IN LAST GENERATION SPARK-IGNITION ENGINES WITHIN THE SPARK-PLUG NO GROUND-ELECTRODES TYPE. - Setyono, Gatot; Arifin, Ahmad Anas (Program Studi Teknik Mesin, Universitas 17 Agustus 1945 Surabaya, 2019)
The objective of this research is to investigate the effect of ethanol-gasoline mixes on the performances of a four-stroke Spark-Ignition engine. Ethanol is observed as an alternative fuel for Spark-Ignition engines and is known for producing blends with gasoline. An experimental investigation was performed on the engine is a four-stroke cycle single-cylinder, engine volume of 124,8 cm3, port fuel injection, a compression ratio of 9,3:1 , and a Euro 3 large-size motorcycle fuelled with commercial gasoline with a Research Octane Number (RON) of 95 and gasoline/ethanol mixes G25, G35, and G45 (range of 25%, 35%, and 45%). The experiments were performed utilizing spark plug no ground-electrodes type, varied engine speeds of 4000-9000 rpm. Regulated and unregulated performances and fuel consumption were measured over the carrying out of chassis-dynamometer tests. The combustion analysis, actualized by taking the pressure cycle inside the cylinder, highlights the autoregulation of the engine control unit and guarantees utilize within the same parameters of various tested fuels, with the besides of fuel injection time, which escalates with increasing ethanol percentage. The maximum power, mean effective pressure and efficiency thermal values were obtained with an ethanol-gasoline mix (G45) the position with operated at 7000 rpm. A significant decrease in specific fuel consumption was observed using an ethanol-gasoline mix of G45 (45%)